Doing God in public: an Anglican interpretation of MacIntyre’s tradition-based reasoning as a Christian praxis for a pluralist world - Rowland Jones, Sarah Caroline (2011)
‘We don’t do God’, Alastair Campbell famously said of UK government policy-making. In contrast, Anglican Bishops at the 2008 Lambeth Conference committed themselves to reflect on contextualising their faith, and pursue their conclusions in public ethical discourse. This thesis proposes that the Bishops (and others) may justifiably pursue this two-fold course, through the application, reinterpretation and development of Alasdair MacIntyre's tradition-based moral reasoning. I contend that the validity of a MacIntyrean approach in contextualising Christianity is readily apparent; and can shed light on Anglican differences around human sexuality. Through distinguishing between MacIntyre’s ‘utopian’ theory and his practical requirement merely to be ‘good enough’ to ‘go on and go further’, I argue that we find effective resources for extensive moral rational engagement with other traditions, and, more surprisingly, within liberal democracy. This, I agree with Jeffrey Stout, has the potential to operate, to a useful degree, as akin to a ‘tradition’. I then outline how the Bishops can best pursue substantive, rational, ethical dialogue, first, with other communities of tradition; second, with those groupings, widespread throughout society, which, though not fully-fledged communities of tradition, nonetheless sufficiently reflect them to be able to sustain some degree of moral debate; and third, through developing MacIntyre's appropriation of Aquinas’ work on Natural Law, in circumstances that, or among those who, uphold no tradition. In each case, I argue the potential is greater than MacIntyre allows, and, importantly, is enhanced by constructive engagement, which it is therefore generally a morally rational obligation to pursue. With examples drawn primarily from the work of Dr Rowan Williams, the Archbishop of Canterbury, I point to practical ways in which my proposed MacIntyrean praxis can both strengthen the Church’s engagement in public discourse, and enhance the nature of the public space as a place for pursuing the common good.